New Technology to improve an Image Compression using the LZW Algorithm - Abed Alwahab, Suad (Al-Iraqia Journal for Scientific Engineering Research, 2023)
Image compression is a process applied to reduce  the   size  of an image file, byte by byte, without reducing its quality  acceptability levels. By reducing the file size, more images can be stored dona given amount of disk or memory space. Thus, bandwidth is required  when images  are transmitted over the Internet or downloaded from a web page, reducing network congestion and speeding contented  delivery. The proposed system adopted the LZW algorithm to compress images without loss. This algorithm was named after the names of the scientists who developed this algorithm in recognition of their efforts, namely Abraham Lempel, Jakob Ziv and Terry Welch, which is based on a dynamic dictionary, where this dictionary checks the file for duplicate data and then stores it in the dictionary, where this algorithm replaces strings of characters with individual symbols, as this proposed system performs 12-bit codes, and it was applied to many images and we got impressive results. The importance of this system lies in the benefit it provides by reducing the size of the image file without losing data, and thus reducing the space needed to store and send it easily over the Internet and  high quality. The Python language has been used to implement this system.